On a new I-convergent sequence space - Khan V. (2017)
The sequence space bv σ was introduced and studied by Mursaleen [10]. In this article we introduce the sequence space BVIσ and study some of the properties of this space. © 2012, by Oldenbourg Wissenschaftsverlag, München, Germany. All rights reserved.